Application of a concurrent grinding technique for two-stage aqueous mineral carbonation. Issue 42 (December 2020) - Rashid, M.I.; Benhelal, E.; Farhang, F.; Oliver, T.K.; Stockenhuber, M.; Kennedy, E.M.
Highlights: Mg extractions almost doubled (71 % vs 39 %). 58 % Mg extraction achieved after 1 h concurrent grinding. Multi-stage grinding increased Mg extractions. Similar extractions using 30 wt% media and reference experiments. Agglomeration increased particle size during second occurrence of grinding. Abstract: Single-stage mineral carbonation is undertaken at relatively high pressures (up to 18 MPa) and high temperatures (up to 185 °C), where in contrast, two-stage mineral carbonation operates at low pressures (<1 MPa) and mild temperatures (<100 °C). This article describes the development of concurrent grinding for application during the initial dissolution stage of the two-stage aqueous mineral carbonation, using heat activated lizardite as feed ore. Various grinding media sizes and concentrations were studied, with 60 wt% grinding media being determined as optimum and engendering 65 % of the Mg in the feed ore being extracted in 2 h compared to 38 % in reference experiments. Mg extraction using a 30 wt% grinding media and in reference experiments were essentially identical, indicating that the use of 30 wt% media is ineffective. Silica-rich layers were observed to be present in the product produced in experiments using 30 wt% media, explaining why the extent of Mg extraction was similar in both experiments. Multi-stage grinding was investigated in an effort to obtain a higher level of Mg extraction. However, it was observed that the average particle size of the ground product increased during the second stage of multi-stage grinding. It is suggested this increase in the average particle size limited the extent of extraction during the second phase of grinding. The particle size increase was determined to be due to the agglomeration of fines and subsequently polyacrylic acid, a commercially available grinding media aid was applied in order to reduce the extent of agglomeration.